Clinical, biochemical and geneticcharacteristics of variegate porphyria in Italy - Di Pierro, E; Ventura, P; Brancaleoni, V; Moriondo, V; Marchini, S; Tavazzi, D; Nascimbeni, F; Ferrari, M C; Rocchi, E; Cappellini, M D (Cellular and Molecular Biology, 2009)
Variegate Porphyria (VP) is an autosomal dominant disorder found worldwide but is rare in Italy. In this study we provide an overview of clinical, biochemical and genetic background of 33 Italian VP patients diagnosed in the last fifteen years. About 70% of patients had experienced clinical symptoms: 43.4% had photosensivity, 8.7% acute attacks and 47.8% both. Among the 33 patients, 14 different mutations were identified. Of these only 6 defects have been previously described in other countries and 8 are unique having been identified for the first time in Italy. Two of these, the c.851G>T and the c.1013C>G, were found in two and four unrelated families respectively. No mutation has been found in homozygosis and no significant correlation has been observed between specific clinical and biochemical manifestations and the type of mutation. In contrast, normal faecal protoporphyrin excretion was high predictive of silent phenotype. Normal urinary excretion of PBG and ALA, predicted absence of neurovisceral symptoms. This paper represents the first compilation of data on genotype-phenotype relation in Italian patients with VP.